2020
DOI: 10.1055/a-1201-7165
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for polyp detection during colonoscopy: a systematic review and meta-analysis

Abstract: Background and study aims: Artificial intelligence (AI)-based polyp detection systems during colonoscopy aim at increasing lesion detection and improving colonoscopy quality. Patients and methods: We performed a systematic review and meta-analysis of prospective trials to determine the value of AI-based polyp detection systems for detection of polyps and colorectal cancer. We performed systematic searches in MEDLINE, EMBASE and Cochrane CENTRAL. Independent reviewers screened studies and assessed eligibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 21 publications
(86 reference statements)
5
120
0
Order By: Relevance
“…CADe is designed to help endoscopists to avoid missing polyps, which might contribute to increasing their ADRs, while CADx is designed to help endoscopists to interpret polyp histology with greater accuracy than endoscopists themselves normally do. The performance of both CADe and CADx has been assessed in several prospective studies, with surprisingly encouraging results, whereas retrospective benchmark tests are considered as suboptimal for accurate assessment of AI tools because of selection bias 7,8 . Additionally, an increasing number of AI products designed for colonoscopy are already available on the market, especially in Europe and Asia.…”
Section: Tackling Challenges In Colonoscopy With Use Of Artificial Inmentioning
confidence: 99%
See 3 more Smart Citations
“…CADe is designed to help endoscopists to avoid missing polyps, which might contribute to increasing their ADRs, while CADx is designed to help endoscopists to interpret polyp histology with greater accuracy than endoscopists themselves normally do. The performance of both CADe and CADx has been assessed in several prospective studies, with surprisingly encouraging results, whereas retrospective benchmark tests are considered as suboptimal for accurate assessment of AI tools because of selection bias 7,8 . Additionally, an increasing number of AI products designed for colonoscopy are already available on the market, especially in Europe and Asia.…”
Section: Tackling Challenges In Colonoscopy With Use Of Artificial Inmentioning
confidence: 99%
“…This number is surprisingly large considering that only around 10 RCTs have been published in the whole medical AI field 16 . Subsequently, two meta‐analyses were published to interpret the impact of these RCTs 7,17 . These meta‐analyses reported that the use of CADe during colonoscopy is likely to increase ADR by ~50%, which may have great benefits in cancer prevention.…”
Section: Randomized Controlled Trials and Meta‐analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…UC-associated dysplasia is often flat with an unclear boundary from the surrounding tissues, making it difficult to detect [2]. AI-based polyp detection systems are used during colonoscopy to increase lesion detection [3]. The EndoBRAIN-EYE system can reportedly identify colorectal lesions with high accuracy in non-UC patients [4,5].…”
Section: A B)mentioning
confidence: 99%